Pengaruh Pemahaman Pendidikan Agama Islam terhadap Pengamalan Keagamaan Siswa Sekolah Menengah Atas Negeri 1 Sangkulirang - Nurhandayani, Sri (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2016)
This research in the wake of the fact that in this time,  students who study Islamic religious education but in himself has not formed Muslim personality, Beginning of dress, speech, association, and other things. In fact, there are still many who have not established conduct religious teachings such as prayer, fasting, and in her social morals less reflects a Muslim student. And do not rule out some that have very broad spiritual  experience  can leave worship and even do things that are religiously forbidden.This research aimed to determine whether there is the effect of understanding islamic education on spiritual  experience  SMA N 1 Sangkulirang. The hypothesis of this study is " theare  is significant effect  among the understanding of Islamic religious education on  spiritual  experience  student SMA N 1 Sangkulirang." That is the better understanding of Islamic education, it would be better of  the spiritual  experience student SMA N I Sangkulirang.The sample collection technique is using cluster random sampling technique on student of SMA N1 class X and XI. While respondents count 104 students. The results obtained show that  understanding of Islamic religious education have the value of  r count of 0.587 with significance value of 0.000. And the count value r is greater than r table (0.578> 0.191), while the value of significance is also smaller than alpha of 0.05 (0.000> 0.05) thus testing showed Ha Ho accepted and rejected. These results show that the variable understanding of Islamic religious education in a positive and significant effect on students' religious practice.R Square results obtained amounted to 0.345 which means that the variable student religious practice can be affected by variables Islam understanding of religious education 34.5%, while the rest is influenced by other variables outside the research.Therefore can be concluded that the understanding of Islamic religious education affect on the  spiritual  experience student. Based on the above findings, the authors suggest to the school in order to further enhance the learning of Islamic education to provide religious understanding and practice to students.